Network anticorrelations, global regression, and phase‐shifted soft tissue correction - Anderson, Jeffrey S. (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Synchronized low‐frequency BOLD fluctuations are observed in dissociable large‐scale, distributed networks with functional specialization. Two such networks, referred to as the task‐positive network (TPN) and the task‐negative network (TNN) because they tend to be active or inactive during cognitively demanding tasks, show reproducible anticorrelation of resting BOLD fluctuations after removal of the global brain signal. Because global signal regression mandates that anticorrelated regions to a given seed region must exist, it is unclear whether such anticorrelations are an artifact of global regression or an intrinsic property of neural activity. In this study, we demonstrate from simulated data that spurious anticorrelations are introduced during global regression for any two networks as a linear function of their size. Using actual resting state data, we also show that both the TPN and TNN become anticorrelated with the orbits when soft tissues are included in the global regression algorithm. Finally, we propose a technique using phase‐shifted soft tissue regression (PSTCor) that allows improved correction of global physiological artifacts without global regression that shows improved anatomic specificity to global regression but does not show significant network anticorrelations. These results imply that observed anticorrelations between TNN and TPN may be largely or entirely artifactual in the resting state. These results also imply that differences in network anticorrelations attributed to pathophysiological or behavioral states may be due to differences in network size or recruitment rather than actual anticorrelations. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.